Kompetensi Sumber Daya Manusia, Teknologi Informasi, dan Laporan Pertanggungjawaban Bendahara dengan Komitmen Organisasi sebagai Pemoderasi - Jumardi, Jumardi; Rajagukguk, Hendriko; Machmury, Andri (E-Jurnal Akuntansi; Vol 32 No 8 (2022)DO - 10.24843/EJA.2022.v32.i08.p06, 2022)
The accountability report is one aspect of the realization of the performance of the expenditure treasurer who plays a role in the accountability of the agency's performance. This study aims to examine and analyze the factors that affect the accuracy of the submission of the expense treasurer accountability report. This type of research is an explanatory research that explains the effect of the independent variable on the dependent variable. Data was obtained through a questionnaire involving 80 respondents consisting of expense treasurers in each work unit in the Makassar I KPPN area, then analyzed using multiple regression with the SPSS tool. The results showed that the competence of human resources and the use of information technology had an effect on the accuracy of the submission of the expenditure treasurer's accountability report. Organizational commitment can moderate the relationship between human resource competence and the use of information technology with the accuracy of the submission of the expense treasurer accountability report. Keywords: Accountability Report; Human Resource Competence; Utilization of Information Technology; Organizational Commitment.